Analisis Gaya Mengajar Guru Dalam Proses Pembelajaran Al-Qur’an Hadis Di MAN 1 Kendari - Kharis Sulaiman Hasri (Al-Riwayah : Jurnal Kependidikan, 2021)
The monotonous teaching style and cooking have made students ineligible for learning. While choosing the right teaching style is the key to an effective learning process. The purpose of this study was to examine the teaching style of teachers in learning the Qur'an Hadith in MAN 1 Kendari. The method used is a qualitative method. The results of this study indicate that the dominant teaching style used by teachers of the Qur'an in MAN 1 Kendari is that all the teachers of al-Al-Hadis use the classical teaching style. However, all teachers issue or integrate classical teaching styles with other teaching styles. Namely using a classical teaching style that is combined with interactional teaching styles and technological teaching styles that are combined with interactional teaching styles